BLADDER TRAINING BERPENGARUH TERHADAP PENURUNAN KEJADIAN INKONTINENSIA URINE PADA PASIEN POST OPERASI BPH DI RUANG RAWAT INAP RSUD SOREANG - Teti Nurhasanah; Ali Hamzah (Jurnal Ilmu dan Teknologi Kesehatan, 2017)
The incidence of benign prostate hyperplasia (BPH) in Indonesia is quite high, which is about 24-30% of urological cases treated in several central public hospitals. While the incidence of BPH in general hospital Soreang in 2014 shows a fairly high incidence rate (12.5 %) and the second number of the top ten surgery cases after fibro adenoma mamma. Open prostatectomy is an invasive treatment to help miction of the BPH patients and it can cause side effects especially urinary incontinence. According to the result of preliminarystudy indicated that 80 % patients who control to Soreang general hospital after open prostatectomy surgery have urinary incontinence. One kind of nursing interventions that can be given to overcome urinary incontinence is by doing bladder training. This study aims to determine the effect of bladder training with use of delay urination and scheduled urination technique to decrease the incidence of urinary incontinence in post operative BPH patients. The research used quasi experiment, with used pre and post test approach in two intervention groups without using control group to 60 samples who obtained by accidental sampling, so the total number of each group is 30 BPH patiens. The results showed that bladder training with both delay urination and scheduled urination techniques had a significant effect on decreasing incidence of urinary incontinence in postoperative BPH patients, but there was no significant difference in the results of the two bladder training techniques on decreasing incidence of urinary incontinence. Related to this result, to prevent urinary incontinence of the post operative BPH patients is suggested to the nurse to apply bladder training with delay urination and scheduled urination techniques and in its application need to considered the age and physical condition of the patient.